2023
DOI: 10.1111/jcmm.17767
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FBXW11 in normal and disease‐associated osteogenic cells

Abstract: The ubiquitin‐proteasome system (UPS) plays an important role in maintaining cellular homeostasis by degrading a multitude of key regulatory proteins. FBXW11, also known as b‐TrCP2, belongs to the F‐box family, which targets the proteins to be degraded by UPS. Transcription factors or proteins associated with cell cycle can be modulated by FBXW11, which may stimulate or inhibit cellular proliferation. Although FBXW11 has been investigated in embryogenesis and cancer, its expression has not been evaluated in os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Transfection of the RUNX2-expressing plasmid was carried out using RUNX2 Lenti ORF particles from Origene Technologies (Rockville, MD, USA), following the manufacturer’s instructions. RUNX2 KO cells were grown to 70% confluence and subsequently transfected with 1.3 µg/mL or 2.6 µg/mL RUNX2-expressing pcDNA3 vector, using the Lipofectamine 3000 reagent (Thermo Fisher Scientific, Waltham, MA, USA; reference: L3000-008), as we previously reported [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transfection of the RUNX2-expressing plasmid was carried out using RUNX2 Lenti ORF particles from Origene Technologies (Rockville, MD, USA), following the manufacturer’s instructions. RUNX2 KO cells were grown to 70% confluence and subsequently transfected with 1.3 µg/mL or 2.6 µg/mL RUNX2-expressing pcDNA3 vector, using the Lipofectamine 3000 reagent (Thermo Fisher Scientific, Waltham, MA, USA; reference: L3000-008), as we previously reported [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA extraction and reverse transcription (RT) were performed using previously reported methods [ 17 ]. Briefly, cells were harvested and total RNA was isolated using the RNeasy ® protect mini kit (Qiagen, Hilden, Germany), according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ubiquitin-proteasome system, which degrades various key regulatory proteins, is crucial for cellular homeostasis. FBXW11 regulates cell proliferation by targeting proteins involved in the cell cycle or those degraded by this system, influencing animal development [21]. Schierding et al's GWAS analysis identified FBXW11 as a crucial modifier of growth, functioning within the regulatory network [22].…”
Section: Genes Associated With the Growthmentioning
confidence: 99%
“…Differential expression analysis showed 12 downregulated genes (mostly associated with the negative regulation of transcription: NFKBIB , BTRC , CREBBP , HDAC1 , NCOR2 , and FBXW11 ) and 19 upregulated genes [mostly associated with protein ubiquitination ( SOCS1 , RBX1 , RPS27A , UBB , UBA52 , and UBE2N ), positive regulation of cell proliferation ( CTNNB1 , NRAS , HRAS , CDKN1A , and STAT3 ), and cell surface receptor signaling pathways ( IL6 , IFNA5 , IFNA7 , IFNA16 , and NGF ) in OS samples compared to controls. Several of these genes have already been associated with OS pathophysiology [ 149 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 ]. Moreover, KEGG functional enrichment was assessed through STRING v12 (available at accessed on 17 April 2024) and showed that under-expressed genes belonged mainly to MAPK and WNT signaling pathways, while upregulated genes belonged to the PI3K/AKT and JAK/STAT cascades ( Figure 6 C), reinforcing the concept of NF-κB as a common player underneath OS establishment and progression.…”
Section: Nf-κb Dysregulation and Cancermentioning
confidence: 99%